Professional PHP Design Patterns - Saray, Aaron (Wrox programmer to programmer, 2009)
PHP is often considered to be the cornerstone for buildingflexible and feature-rich web applications. Because of its relatively simple initial learning curve, newer programmers can easily create applications in PHP from the ground up. As these applications scale, however, the maintenance can seem daunting. Luckily, the mature programming community has something to offer: Design Patterns. These repeatable solutions for common problems have been applied for years to other programming languages. This book aims to bridge the gap between the PHP and the older programming language by applying those tried and tested Design Patterns to native PHP applications. This book starts with an introduction to Design Patterns, describes their use and importance, and details where you've seen them already. It continues through a host of Design Patterns with code examples and explanations. Finally, an in-depth case study shows you how to plan your next application using Design Patterns, how to program those patterns in PHP, and how to revise and refactor an existing block of code using Design Patterns from the book. The author approaches the concepts in technical yet usable formats that are familiar to both programmers who are self-taught and those with more extensive formal education. What you will learn from this book What Design Patterns are and why they matter in PHP Commonly established PHP Library usage of Design Patterns Faster and more efficient object creation with Design Patterns like Builder, Façade, Prototype and Template Decoupled architecture using Data Access Object and Proxy Design Patterns Better code flow and control using the Delegate, Factory and Singleton Design Patterns How to implement Visitor and Decorator Design Patterns to enhance objects without modifying their core Comprehensive plug-in creation techniques using Observer Design Pattern How to plan application architecture using Design Patterns How to program a case study web site from start to finish with Design Pattern based coding How to recognize architectural benefits from Design Patterns in an existing application Methods to further strengthen code from case study analysis Who this book is for This book is for experienced PHP programmers who are looking to enhance the quality of their code architecture with Design Patterns. Wrox Professional guides are planned and written by working programmers to meet the real-world needs of programmers, developers, and IT professionals. Focused and relevant, they address the issues technology professionals face every day. They provide examples, practical solutions, and expert education in new technologies, all designed to help programmers do a better job. Updates, source code, and Wrox technical support at www.wrox.com.